Quality of life in patients with coronary heart disease associated with metabolic syndrome: Results of factor analysis - V V Kaliuzhin; A T Tepliakov; N V Riazantseva; I D Bespalova; D Iu Kamaev; E V Kaliuzhina (Терапевтический архив, 2012)
AIM: To identify the factors most substantially influencing the quality of life (QL) in patients with coronary heart disease (CHD) associated with metabolic syndrome (MS), by using the principal component method. /MATERIAL AND METHODS: One hundred and two male patients (mean age 48.6±1.02 years) with CHD associated with MS, who had experienced large-focal myocardial infarction not earlier than 6 months before, were examined. Estimation of QL (EORTC QLQ CORE 30) and emotional-personal sphere (brief multifactorial personality questionnaire test and Spielberg's trait anxiety inventory) was made along with the complete clinical, laboratory, and instrumental examination accepted in specialized clinical practice of cardiology /RESULTS: A factor analysis of the variables obtained after a thorough examination of the patients could identify 4 common QL determinants, such as postinfarction cardiac remodeling, neurotization, obesity, and the degree of heart and coronary failure /CONCLUSION: MS in patients with CHD appreciably determines the total score of physical, emotional, and social well-being. In the cluster of MS components, obesity is a major factor that influences QL in patients who have sustained myocardial infarction.